Pengaruh Layanan Informasi Media Padlet Terhadap Pemahaman Covid-19 Pada Siswa Kelas X SMAN 1 Batu Layar - Maris Ramdhani Saputro; Ni Ketut Alit Suarti; Jessica Festy Maharani (Masyarakat Cita Insani (YAMACITA) Bergerak Dibidang Penelitian, Pendidikan, Pelatihan, Research, 2026)
This study aims to determine the effect of information services delivered via the Padlet platform on students' understanding of COVID-19. The study was motivated by students' limited understanding of health information and the suboptimal use of digital media in guidance and counseling services. A quantitative approach was employed using a pre-experimental, one-group pre-test/post-test design. The sample consisted of 31 Grade X students from SMAN 1 Batu Layar, selected using a total sampling technique. Data were collected via a COVID-19 understanding questionnaire and analyzed using a t-test. The results revealed a calculated t-value of 9.405, which exceeded the t-table value of 2.042 at a significance level of 0.05. This indicates that Padlet-based information services significantly improved students' understanding of COVID-19. Thus, digital media offers an innovative alternative for enhancing the effectiveness of school guidance and counseling services.